The Digital Sabbath and Digital Distraction - Paris, Lisa; Morris, Julia; Nykiel, Annette (Australian Council of University Art and Design Schools, 2019)
Upheavals in social media and communications are overturning education, at the same time, a group of art education graduates and their artist lecturers are using creative research to disrupt this turn by visualising the practice of Digital Sabbath. The Digital Sabbath practice aimed to explore the feasibility of switching off from technology and the impact of this practice on the participants, and those around them.